The relationship between the tumour stroma percentage, clinicopathological characteristics and outcome in patients with operable ductal breast cancer - Gujam, F J A (Nature Publishing Group, 2014)
BACKGROUND: The percentage of tumour stroma (TSP) has recently been reported to be a novel independent predictor of outcome in patients with a variety of common solid organ tumours. The aim of this study was to examine the relationship between TSP, clinicopathological characteristics and outcome in patients with invasive ductal breast cancer, in particular node negative and triple negative disease. METHODS: A total of 361 patients with primary operable invasive ductal breast cancer were included in this study. The TSP was assessed visually on the haematoxylin and eosin-stained tissue sections. With a cutoff value of 50% TSP, patients with ⩽50% stroma were classified as the low-TSP group and those with >50% stroma were classified as the high-TSP group. RESULTS: A total of 109 (30%) patients had high TSP. Patients with high TSP were old age (P=0.035), had more Her-2-positive tumours (P=0.029), low-grade tumour inflammatory infiltrate (P=0.034), low CD68+macrophage infiltrate (P<0.001), low CD4+ (P=0.023) and low CD8+ T-lymphocytes infiltrate (P=0.017), tumour recurrence (P=0.015) and shorter cancer-specific survival (P<0.001). In node-negative patients (n=207), high TSP was associated with low CD68+macrophage infiltrate (P=0.001), low CD4+ (P=0.040) and low CD8+ T-lymphocytes infiltrate (P=0.016) and shorter cancer-specific survival (P=0.005). In triple negative patients (n=151), high TSP was associated with high tumour grade (P=<0.001), lymph node positivity (P=0.027), low CD68+macrophage infiltrate (P=0.011) and shorter cancer-specific survival (P=0.035). The 15-year cancer-specific survival rate was 79% vs 21% in the low-TSP group vs high-TSP group. In multivariate survival analysis, a high TSP was associated with reduced cancer-specific survival in the whole cohort (P=0.001), node-negative patients (P=0.007) and those who received systemic adjuvant therapy (P=0.021), independent of other pathological characteristics including host inflammatory response. However, TSP was not an independent prognostic factor for triple negative patients (P=0.151). CONCLUSIONS: A high TSP in primary operable invasive ductal breast cancer was associated with recurrence and poorer long-term survival. The inverse relation with the tumour inflammatory infiltrate highlights the importance of the amount of tumour stroma on immunological response in patients with primary operable ductal breast cancer. Implementing this simple and reproducible parameter in routine pathological examination may help optimise risk stratification in patients with invasive ductal breast cancer.